2001
DOI: 10.1023/a:1012338828418
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to determine if a relationship exists between nonalcoholic steatohepatitis (NASH) and serum levels of free fatty acids, choline deficiency, or celiac disease. Forty-seven patients with liver biopsy proven NASH were enrolled. Total serum free fatty acids and anti-endomysial antibodies were determined in all patients, while plasma free and phospholipid-bound choline were determined in 29 patients. Total serum free fatty acid concentration correlated significantly with female gender and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…PUMA Is Up-regulated in Human NASH-Clinically, circulating FFA are elevated in the metabolic syndrome and in patients with NASH (15). PUMA expression was assessed in human liver specimens, comparing obese normal control liver specimens to those with simple steatosis and steatosis plus inflammation (NASH).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PUMA Is Up-regulated in Human NASH-Clinically, circulating FFA are elevated in the metabolic syndrome and in patients with NASH (15). PUMA expression was assessed in human liver specimens, comparing obese normal control liver specimens to those with simple steatosis and steatosis plus inflammation (NASH).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated serum FFA levels and hepatocyte apoptosis are hallmarks of NASH, and levels of circulating FFA correlates with liver disease severity (14,15). Prior studies have identified structural and functional mitochondrial abnormalities (48,67,68) as well as an endoplasmic reticulum stress-induced JNK activation in liver cells from NASH patients (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current concepts indicate that FFA, and not their esterified product (triglyceride), mediate hepatic lipotoxicity (11,12). Elevated serum FFA correlate with liver disease severity (13)(14)(15), and therapies that enhance insulin sensitivity ameliorate hepatic lipotoxicity, in part, by decreasing plasma FFA (16). Hepatic FFA also accumulate in experimental steatohepatitis, further supporting a role for these nutrients in hepatic lipotoxicity (17).…”
mentioning
confidence: 99%